Finding incident cancer cases through outpatient oncology clinic claims data and integration into a state cancer registry - Cogle1, Christopher R.; Levin, Gary; Lee, David J.; Peace, Steven; Herna, Megsys C.; MacKinnon, Jill; Gwede, Clement K.; Philip, Celeste; Hylton, Tara (Cancer causes & control, 2021)
Cancer data from population-based cancer registries under-report cancer cases, especially for cancers primarily diagnosed and treated in outpatient clinical settings, away from hospital-based cancer registrars. Previously, we developed alternative methods of cancer case capture including a claims-based method, which identified a large proportion of cancer cases missed by traditional population-based cancer registries. In this study, we adapted a claims-based method for statewide implementation of cancer surveillance in Florida. Between 2010 and 2017 the claims-based method identified 143,083 cancer abstracts, of which 42% were new and 58% were previously registered. The claims-based method led to the creation of 53,419 new cancer cases in the state cancer registry, which made up 9.3% of all cancer cases registered between 2010 and 2017. The types of cancers identified by the claims-based method were typical of the kinds primarily diagnosed and treated in outpatient oncology clinic settings, such as hematological malignancies, prostate cancer, melanoma, breast cancer, and bladder cancer. These cases were added to the Florida cancer registry and may produce an artefactual increase in cancer incidence, which is believed to be closer to the actual burden of cancer in the state.